Biomimetic and engineered surfaces for atmospheric water harvesting: Principles, fabrication, and applications - Taghreed Abdulhameed Al-Gunaid (22963000) (2025)
This research paper focuses on a recent review of water harvesting and transport mechanisms on the patterned surfaces inspired by creatures adapted for living in harsh environments with extreme water scarcity, such as the Namib Desert beetle (Stenocara gracilipes). The most notable adaptation of the Namib beetle is its ability to harvest water from fog, which occasionally rolls from the ocean. The beetle's elytra are designed to possess two wettability extremes: small hydrophilic (water-attracting) bumps and large hydrophobic areas, enabling the transportation of collected water. Tiny water droplets are condensed on hydrophilic bumps and rolled down along the beetle's body to its mouthparts, allowing its survival in hostile environments. The beetle's unique approach to collecting water from fog has inspired biomimicry and technological developments in efficient water harvesting in arid regions, such as the use of biomimetic materials to capture and collect water from the atmosphere. This review highlights the fundamental principles of a wettability-driven water harvesting system, focusing on the development of functional bio-mimicking patterned materials inspired by Nature. First, the theoretical aspects of the wetting mechanisms of biomimetic surfaces are outlined. Furthermore, it reviews the practical applications and technical challenges associated with the developed patterned system, comprising water harvesting, anti-icing, oil-water separation, and biosensing technologies. Various technologies for designing bioinspired materials with maximal water collection efficiency are classified and described. Finally, it addresses the development of potential approaches and technological solutions for wettability-patterned systems derived from nature-inspired systems. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.117514